Daya Terima dan Kandungan Gizi Kue Sapik dengan Subsitusi Tepung Kacang Hijau dan Penambahan Daun Kelor sebagai Snack Tinggi Energi dan Protein - Ingkasari Salamao; Rita Ismawati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Mung beans and moringa leaves are food ingredients rich in energy and protein. These ingredients can be utilized by substituting mung bean flour and adding moringa leaves in the production of sapik cake. This study aims to determine the effect of mung bean flour substitution and moringa leaf addition on the acceptability (color, aroma, texture, and taste) and nutritional content of sapik cake as an alternative high-energy, high-protein snack. This research employed a true experimental design with a Completely Randomized Design (CRD) method. The formulations consisted of mung bean flour at 10 g, 15 g, 20 g, and 25 g, combined with moringa leaves at 5 g and 7 g, resulting in four different formulas. Data collection used a hedonic test on a 1–6 scale with 30 semi-trained panelists. Data analysis was conducted using the Kruskal-Wallis test and the Mann-Whitney post hoc test. The results showed significant effects on aroma, texture, and taste. The best formulation was H1K1, containing 10 g mung bean flour and 5 g moringa leaves. Its nutritional content per 100 g included 362.13 kcal energy, 15.76 g protein, 48.98 g carbohydrates, and 7.47 g fat.